The effect of internet attention to stock returns and volumes in Finland - Harjunpää, Hanna (My University, 2019)
Internet has revolutionized the possibilities to find and gather information. It has a prevalent role as an intermediary between companies and investors. However, the huge amount of information makes it challenging to filter the information which is actually relevant and reliable. This fact is the reason, why search engines are so used tools nowadays. They reduce the time required to find the needed information from the huge amount of different sources. Google searches reflect the interests of the people using it and thus it can be a very useful tool for measuring interest of investors towards certain objects or matters. This thesis is examining the effect of changes in investor attention, more precisely changes in Google search volume indices (GSVI), to the returns and volumes of selected finnish stocks. It is hypothesized that higher amount of searches with a company name means higher investor interest towards the stock and thus higher returns and volumes on a short term. Additionally, the study reports whether the effect is different between small and big companies. This thesis investigates a panel data of 46 finnish companies from technology, finance and consumer goods sectors from October 2013 to September 2018 and search volumes for company names. The stock market data is acquired from Helsinki Stock Exchange database and search volume indices from Google Trends. The result of the study revealed a connection between search volumes and both stock returns and volumes in Finland. The magnitudes of the coefficients stayed quite modest but statistically significant. The relationship between both returns and volumes was positive with the one week lag in GSVI but negative with two weeks lag. The effect of change in internet attention was shown to be stronger for small companies than for big companies when considering the return but no statistically significant difference was found when considering the volume.
Keywords: Internet attention, Search volume, Behavioral Finance; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance